THE IMPORTANCE OF DEVELOPING SMALL AND MEDIUM-SIZED CITIES IN UZBEKISTAN - Kurbanaliyeva H. I. (American Journals Publishing, 2024)
The article describes the socio-economic migration situation expected in Uzbekistan and the opportunities related to resources, which motivate the development of small and medium-sized cities, and the importance of controlling and scientifically managing this process.
Keywords: Small and medium-sized cities, agglomeration, capital city, urban sociology, sociological studies with monitoring of the